Is a low level of free thyroxine in the maternal circulation associated with altered endothelial function in gestational diabetes? - Guzmán-Gutiérrez, Enrique; Veas, Carlos; Leiva, Andrea; Escudero, Carlos; Sobrevia, Luis (Frontiers in Pharmacology, 2014)
Synthesis of thyroid hormones, thyroxine (T4) and tri-iodothyronine (T3), in the human fetus starts from 17-19th weeks of gestation. Despite the majority of normal pregnant women reaching adequate levels of circulating thyroid hormones, in some cases, women with normal pregnancies have low level of free T4 during first trimester of pregnancy, suggesting that T4 action may be compromised in those women and their fetuses. In addition, pathological low levels of thyroid hormones are detected in isolated maternal hypothyroxemia (IMH) and clinical hypothyroidism. Nevertheless, human placenta regulates T3/T4 concentration in the fetal circulation by modulating the expression and activity of both thyroid hormone transporters (THT) and deiodinases. Then, placenta can control the availability of T3/T4 in the feto-placental circulation, and therefore may generate an adaptive response in cases where the mother courses with low levels of T4. In addition, T3/T4 might control vascular response in the placenta, in particularly endothelial cells may induce the synthesis and release of vasodilators such as nitric oxide (NO) or vasoconstrictors such as endothelin-1 mediated by these hormones. On the other hand, low levels of T4 have been associated with increase in gestational diabetes (GD) markers. Since GD is associated with impaired placental vascular function characterized by increased NO synthesis in placental arteries and veins, as well as elevated placental angiogenesis, it is unknown whether reduced T4 level at the maternal circulation could result in an altered placental endothelial function during GD. In this review, we analyze available information regarding thyroid hormones and endothelial dysfunction in GD; and propose that low maternal levels of T4 observed in GD may be compensated by increased placental availability of T3/T4 via elevation in the activity of THT and/or reduction in deiodinases in the feto-placental circulation.